Rethinking the cuban revolution. Raúl Castro's presidency (2008-2013) - Hernández, David (Papeles de Europa, 2016)
In the present dissertation, we analyze the presidency of Raúl Castro, after his brother Fidel Castro left power. The years of government of the new president have been marked by a series of deep reforms that have altered the political and economic dynamics of the island. The Cuban regime lives turbulent times, where the state tries to respond to international changes and transformation of Cuban society, without altering the basic principles of the 1959 revolution. Certainly, Raul Castro's mandate is marking the present and future of the Caribbean country.
Keywords: reforms; cuban regime; Raúl Castro; socialist state